2017
DOI: 10.1038/srep45263
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial lymphatic capillary expansion impacts on plaque T cell accumulation in atherosclerosis

Abstract: During plaque progression, inflammatory cells progressively accumulate in the adventitia, paralleled by an increased presence of leaky vasa vasorum. We here show that next to vasa vasorum, also the adventitial lymphatic capillary bed is expanding during plaque development in humans and mouse models of atherosclerosis. Furthermore, we investigated the role of lymphatics in atherosclerosis progression. Dissection of plaque draining lymph node and lymphatic vessel in atherosclerotic ApoE−/− mice aggravated plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
2
56
1
Order By: Relevance
“…In atherosclerotic lesions, macrophage foam cells have been suggested as a significant source of lymphangiogenic VEGF-C 110 . Similar findings have been reported for other atherosclerotic arteries in humans, including iliac arteries 111,112 , and the abdominal aorta, where adventitial lymphatic densities were increased and correlated with intimal thickness, notably in advanced or ruptured atherosclerotic lesions 113 , where also VEGF-D expression may be increased 114 .…”
Section: Vascular Lymphangiogenesis In Atherosclerosissupporting
confidence: 87%
See 3 more Smart Citations
“…In atherosclerotic lesions, macrophage foam cells have been suggested as a significant source of lymphangiogenic VEGF-C 110 . Similar findings have been reported for other atherosclerotic arteries in humans, including iliac arteries 111,112 , and the abdominal aorta, where adventitial lymphatic densities were increased and correlated with intimal thickness, notably in advanced or ruptured atherosclerotic lesions 113 , where also VEGF-D expression may be increased 114 .…”
Section: Vascular Lymphangiogenesis In Atherosclerosissupporting
confidence: 87%
“…Interestingly, therapeutic inhibition of plaque lymphangiogenesis, by overexpression of a VEGF-C/VEGF-D trap, led to accelerated atherosclerosis in the descending aorta in both ApoE-deficient and in atherogenic LDLR −/− /ApoB 100/100 mice 108,116 . Similarly, it was recently reported that surgical dissection of aortic plaque-draining lymph nodes led to aggravated plaque formation in ApoE-deficient mice, including increased intraplaque and adventitial T cell densities 113 . Further, a potential role for additional lymphangiogenic factors in plaque lymphangiogenesis was shown by local silencing of the CXCL12 (SDF-1α) chemokine in the carotid artery of ApoE-deficient mice, which resulted in reduced adventitial lymphangiogenesis and increased T cell density 113 .…”
Section: Vascular Lymphangiogenesis In Atherosclerosismentioning
confidence: 80%
See 2 more Smart Citations
“…Atherosclerosis and its cardiovascular consequences claim more lives than all types of cancer combined and it represents an enormous health care burden in western societies [10,11]. In recent years, the lymphatic network has attracted the attention of vascular biologists due to its role in immune cell trafficking, removal of cholesterol-loaded HDL from the periphery via reverse cholesterol transport (RCT), and the regulation of the inflammatory response in general [12,13,14,15,16]. Previous studies demonstrated the presence of LVs in atherosclerotic arteries, yet, our knowledge about the mechanisms regulating lymphangiogenesis and lymphatic function in the vessel wall and the role of LVs in the pathogenesis of atherosclerosis is limited.…”
Section: Introductionmentioning
confidence: 99%